Beyond the Flow, from Tape to Digital: Insights from Mediaset's Archives - Emiliano Rossi (VIEW Journal of European Television History and Culture, 2024)
This study delves into the evolution of Mediaset’s audiovisual archive, tracing its development from a mere storage facility to a sophisticated digital repository. It examines the strategic importance of archives in the television industry, focusing on the retrieval, storage, cataloguing, and commercial re-use of TV content. The paper highlights the implementation of AI and automation in managing digital resources, and the unique model adopted by Mediaset for content retention. The analysis underscores the logistical, technological, and organisational functions of the archives, and their impact on production, distribution, and long-term preservation processes.